Elucidating the biological basis for the reinforcing actions of alcohol in the mesolimbic dopamine system: the role of active metabolites of alcohol - Deehan, Gerald A.; Hauser, Sheketha R.; Wilden, Jessica A.; Truitt, William A.; Rodd, Zachary A. (Frontiers in Behavioral Neuroscience, 2013)
The development of successful pharmacotherapeutics for the treatment of alcoholism is predicated upon understanding the biological action of alcohol. A limitation of the alcohol research field has been examining the effects of alcohol only and ignoring the multiple biological active metabolites of alcohol. The concept that alcohol is a ‘pro-drug’ is not new. Alcohol is readily metabolized to acetaldehyde within the brain. Acetaldehyde is a highly reactive compound that forms a number of condensation products, including salsolinol and iso-salsolinol (acetaldehyde and dopamine). Recent experiments have established that numerous metabolites of ethanol do have direct CNS action, and could, in part or whole, mediate the reinforcing actions of alcohol within the mesolimbic dopamine system. The mesolimbic dopamine system originates in the ventral tegmental area (VTA) and projects to forebrain regions that include the nucleus accumbens (Acb) and the medial prefrontal cortex (mPFC) and is thought to be the neurocircuitry governing the rewarding properties of drugs of abuse. Within this neurocircuitry there is convincing evidence that; 1) biologically active metabolites of alcohol can directly or indirectly increase the activity of VTA dopamine neurons, 2) alcohol and alcohol metabolites are reinforcing within the mesolimbic dopamine system, 3) inhibiting the alcohol metabolic pathway inhibits the biological consequences of alcohol exposure, 4) alcohol consumption can be reduced by inhibiting/attenuating the alcohol metabolic pathway in the mesolimbic dopamine system, 5) alcohol metabolites can alter neurochemical levels within the mesolimbic dopamine system, and 6) alcohol interacts with alcohol metabolites to enhance the actions of both compounds. The data indicate that there is a positive relationship between alcohol and alcohol metabolites in regulating the biological consequences of consuming alcohol and the potential of alcohol use escalating to alcoholism.